2005
DOI: 10.1002/micr.20132
|View full text |Cite
|
Sign up to set email alerts
|

Delayed microsurgical reconstruction of the extremities for complex soft-tissue injuries

Abstract: The treatment of severe wounds of the extremities, characterized by large posttraumatic tissue loss, represents a clinical problem difficult to resolve, especially when the lesion is surrounded by large areas of ischemic distrophic tissue which progressively aggravate and extend the initial lesion, with frequent exposure of bone and joint structures making the amputation of the limb an inevitable outcome. The authors present their experience based on combined treatments by medical support methods such as hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Previous studies suggested the VAC treatment to stimulate angiogenesis and the ingrowth of granulation tissue [48,49]. Up to date, two studies have examined the effect of a combined HBO and VAC therapy on wound healing [50,51] in reconstructive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested the VAC treatment to stimulate angiogenesis and the ingrowth of granulation tissue [48,49]. Up to date, two studies have examined the effect of a combined HBO and VAC therapy on wound healing [50,51] in reconstructive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…This flap is simpler to use compared to a free flap and may be transferred with a reliable pedicle with satisfactory cosmetic outcome of the donor site. Adequate coverage of the soft-tissue and bone defect after debridement may be ensured due to optimal tissue vascularisation, removing dead space, improving vascularity and enhancing leukocyte function [7,9], as well as avoiding the risk of vascular steal syndrome when the anterior tibial artery is damaged. However, the Soleus muscle may not be available due to high energy trauma or subsequent infection and may cause further motor function loss to an existing injured lower limb [6].…”
Section: After 2 Months In the Absence Of Infection A Vascularisedmentioning
confidence: 99%
“…Literature has described treatment "guidelines" regarding severe lesions of the lower limbs, with aggressive debridement of devitalised and contaminated tissue to reduce the rate of nonunion, osteomyelitis and amputation [6,7] as well as the use of free flap transfer, within 24-72 hours [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The timing of soft tissue reconstruction after lower extremity trauma is not well detailed in the literature. It is defined as preferably within 2 weeks of the injury; however, the patient should be medically optimized and the wounds clean [ 1 , 10 ]. If this is not the case, it is advisable to delay the time to reconstruction by employing neoadjuvant therapies such as hyperbaric oxygen (HBO) therapy or vacuum-assisted closure (VAC) therapy, and to perform further debridement to clean the wound [ 10 ].…”
Section: Introductionmentioning
confidence: 99%